Water-soluble matter mediated phototransformation of guaiacol leading to formation of aqueous secondary organic aerosol: Mechanism and kinetics - Jiayi Wang; Rui Zeng; Jun He; Chengjun Wang (Journal of Environmental Sciences, 2026)

Homogeneous integrated design of polyurethane-based hydrogel electrolytes and electrodes for stretchable supercapacitor - Qingkun Tang; Chengjun Yu; Zuyun Chen; Sisi Yang; Jianxin Tang; Yanqing Li; Songshan Zeng; Xiaoyuan Yu (Chemical Engineering Journal, 2026)

Spatial heterogeneity, source apportionment and ecological risks of trace metal(loid)s in lakes across China - Xue Li; Weijie Yao; Hui Zeng; Xuan Hou; Bin Wang; Xing Yang; Chengjun Ge; Hailong Zhou; Jiwei Luo; Xueqiang Lu (Journal of Hazardous Materials, 2026)

A critical review of microbial electrochemical systems for uranium remediation: Bioelectrochemical reduction, resource recovery, and sustainability considerations - Jingyi Wang; Ziyin Xia; Liyao Zeng; Leyi Chen; Yiming Jiang; Guanzhen Chen; Chengjun Guo; Jiaqian Zhang; Weiquan Deng; Chenxi Li; Meng Li; Hongguo Zhang (Journal of Environmental Chemical Engineering, 2026)

Critical bistability in variable cross-section metamaterials: PINN-driven transient stress recognition and adaptive energy dissipation - Jian Zhou; Chengjun Zeng; Wei Zhao; Jinsong Leng; Yanju Liu (Chemical Engineering Journal, 2026)

Long-term natural photodegradation of plastic films enhances the molecular complexity of plastic-derived dissolved organic matter - Derong Zhang; Jiwei Luo; Xue Li; Dongming Wu; Yanhai Xie; Hui Zeng; Hui Deng; Qingmian Chen; Chengjun Ge; Ying Zhang (Water Research, 2026)

Linking plant traits, soil nutrients, climate and soil microbes in temperate grasslands - Yunlong Hu; Gukailin Ao; Liangchen Fu; Chengjun Ji; Hui Zeng; Biao Zhu (Plant and Soil, 2025)

Synergistic dynamic pitch and incoherent scattering enabling programmable cellulose thermochromic hybrids with UV–Vis-NIR broad modulation and multifunctionality - Binhong Yu; Ziyan Chen; Zhiyuan Sun; Chengjun Yu; Zhenni Lu; Songshan Zeng (Chemical Engineering Journal, 2025)

4D printed kirigami metamaterial with reconfigurability for dual-mode displacement-pressure sensing - Song Liu; Zhaoxuan Niu; Wei Zhao; Chengjun Zeng; Yanju Liu; Jinsong Leng (Chemical Engineering Journal, 2025)

Climate, plant and microorganisms jointly influence soil organic matter fractions in temperate grasslands - Yunlong Hu; Liangchen Fu; Gukailin Ao; Chengjun Ji; Hui Zeng; Biao Zhu (Science of The Total Environment, 2025)

4D printed mortise-tenon mechanical-electromagnetic multifunctional pixel metamaterials - Xiaozhou Xin; Chunli Yang; Zhicheng Wang; Yin Xing; Chengjun Zeng; Liwu Liu; Yanju Liu; Jinsong Leng (Chemical Engineering Journal, 2025)

Electrically conductive functionalization of cured polyether ether ketone with improved bioactivity by surface-polymerization of polyaniline - Xuelian Wu; Yang Zhou; Jian Yang; Xiongjie Liang; Yuanrong Xin; Qian Yang; Guanghua Chen; Chengjun Zeng; Xin Lan; Wei Zhao; Yanju Liu (Chemical Engineering Journal, 2024)

M6PR interacts with the HA2 subunit of influenza A virus to facilitate the fusion of viral and endosomal membranes - Yuzhen Hu; Li Jiang; Guangwen Wang; Yangming Song; Zhibo Shan; Xuyuan Wang; Guohua Deng; Jianzhong Shi; Guobin Tian; Xianying Zeng; Liling Liu; Hualan Chen; et al. (Science China Life Sciences, 2024)

Diesel soot combustion in air-NO environment: Evolution of soot physical properties and fragmentation characteristics - Jiangjun Wei; Chengjun He; Yang Zeng (Science of The Total Environment, 2024)

Regulation of electrical properties via ferroelectric polarization for high performance Sb2Te3 thermoelectric thin films - Boyu Yang; Yubo Luo; Chengjun Li; Wang Li; Chengwei Sun; Zheng Ma; Yongxin Qian; Xianwei Zeng; Yingchao Wei; Haiqiang Liu; Dan Zhang; Xin Li; et al. (Chemical Engineering Journal, 2023)

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Vaccination of poultry successfully eliminated human infection with H7N9 virus in China - Xianying Zeng; Guobin Tian; Jianzhong Shi; Guohua Deng; Chengjun Li; Hualan Chen (Science China Life Sciences, 2018)

Methodology for antibody preparation and detection of southern rice black-streaked dwarf virus - Zhuo Chen; Chengjun Yin; Jiaju Liu; Mengjiao Zeng; Zhenchao Wang; Dandan Yu; Liang Bi; Linhong Jin; Song Yang; Baoan Song (Archives of Virology, 2012)

Comparative analyses of leaf anatomy of dicotyledonous species in Tibetan and Inner Mongolian grasslands - JianJing Ma; ChengJun Ji; Mei Han; TingFang Zhang; XueDong Yan; Dong Hu; Hui Zeng; JinSheng He (Science China Life Sciences, 2012)